Presurgical Comorbidities as Risk Factors For Chronic Postsurgical Pain Following Total Knee Replacement. Issue 7 (July 2019) - Skrejborg, Peter; Petersen, Kristian K.; Kold, Søren; Kappel, Andreas; Pedersen, Christian; Østgaard, Svend E.; Simonsen, Ole; Arendt-Nielsen, Lars
Abstract : Objectives: Chronic postsurgical knee pain (CPSP) is a burden for ∼20% of the patients following total knee replacement (TKR). Presurgical pain intensities have consistently been found associated with CPSP, and it is suggested that comorbidities are likewise important for the development of CPSP. This study aimed to identify presurgical risk factors for the development of CPSP 5 years after TKR on the basis of medical records containing information with regard to comorbidities. Materials and Methods: Patients undergoing primary TKR surgery were contacted 5 years after TKR. Presurgical Knee Society Score and comorbidities were evaluated. Postsurgical knee pain at 5 years of follow-up was assessed on a Numeric Rating Scale (NRS, 0 to 10). Logistic regression models were utilized to identify patients with moderate-to-severe (NRS≥3) and mild-to-no (NRS<3) CPSP at 5-year follow-up. Odds ratio (OR) for significant factors was calculated. Results: A total of 604 patients were contacted, 493 patients responded, 352 patients provided a completed questionnaire. A total of 107 patients reported NRS≥3 at follow-up. Significant presurgical factors associated with CPSP were fibromyalgia (OR=20.66; P= 0.024), chronic pain in body parts other than the knee (OR=6.70; P= 0.033), previous diagnosis of cancer (OR=3.06; P= 0.001), knee instability (OR=2.16; P= 0.021), younger age (OR=2.15; P= 0.007), and presurgical knee pain (OR=1.61; P= 0.044). Regression analysis identified 36 of 107 (33.6%) patients with CPSP on the basis of presurgical factors, and 231 patients (94.3%) without CPSP were classified correctly. Discussion: The current study found that a variety of presurgical clinical factors can correctly classify 33.6% of patients at risk for developing CPSP 5 years following TKR.